RELATIONSHIP BETWEEN SEQUENCE STRATIGRAPHY AND RELATIVE SEA-LEVEL CHANGES - Jamaluddin Jamaluddin; Romuald Sohores; Muhammad Fawzy Ismullah Massinai (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2017)
The continuous sea-level rise will result in conditions where the level of accommodation space is greater than that of sediment supply produced undertransgression conditions. When the sea level reaches its maximum point, the sedimentation rate will exceed the sea level rise and aggrades becomes more dominant progradation will result in new Highstand System Tract (HST) condition. Keyword: Accommodation, Sea level changes, Sedimentation, Sequence, Stratigraphy